Relacoes entre a concentracao espacial dos ramos industriais 'motrizes' e o desenvolvimento regional: o caso do Estado de Sao Paulo. - Sampaio, S. S. (My University, 1983)
This paper, having its conceptual basis in the Theory of Growth Poles, by F.Perroux, tests the effective existence of correlation between the spatial incidence and concentration of the 'propulsive' industrial groups and the industrial growth as a whole and the demographic increase. The selected case study was the state of Sao Paulo and data used was the 1970 census. As consequence of the techniques applied a industrial regionalization of the 'paulista' space was obtained, showing few areas of intense industrial concentration, especially of 'propulsive' groups, with multiple growth poles, and large areas with industrial rarefaction, with little or no poles.-after English summary
Relationships between spatial concentration in two propulsive industrial sectors and regional development: the case of Sao Paulo State, Brazil